GLOBAL DEMOGRAPHIC CHANGES AND THE FACTOR OF POLITICAL CULTURE - Yuri Borysovych Pribytkov (Science and Innovation Center Publishing House, 2017)
In an article in the context of the demographic transformation of the political and social landscape of the world, as well as in the socio-political situation reactionary response to demographic change factor considers the problem of political culture. The author proposes to look at the demographic transformation of the system of political and social landscape of the world from the perspective of the use of means of social power in the global political process.